Seroprevalence of Hepatitis A and Hepatitis E Viruses among Pregnant Women in Northern Iran. (3rd July 2021) - Sadeghi, Farzin; Golchob, Zahra; Javadian, Maryam; Barary, Mohammad; Sabbagh, Parisa; Ebrahimpour, Soheil; Bayani, Masomeh
Abstract : Background . Hepatitis A (HAV) and hepatitis E viruses (HEV) are endemic in Iran and are known major causes of acute viral hepatitis. Also, during pregnancy, they are associated with severe outcomes. Therefore, it is vital to evaluate the antibody levels against HAV and HEV in pregnant women to avoid severe outcomes incidence. Study design and methods . A total of 247 pregnant women were enrolled in this prospective cross-sectional study. In addition to completing the questionnaire and interviewing all participants, the serum samples were tested for anti-HAV and anti-HEV IgG using the enzyme-linked immunosorbent assay (ELISA). The association between anti-HAV and anti-HEV antibodies status and risk factors was evaluated. Results . The mean age of patients was 28.06 ± 5.29 years. Anti-HAV antibody was found in 111 patients (44.9%), while anti-HEV antibody was detected in only two pregnant women (0.8%). The seroprevalence of HAV was inversely related to the level of education. There was no significant correlation between HAV antibody levels and age, marital status, residence location, and pregnancy trimesters. Conclusion . Considering many complications of these diseases in pregnancy, the detection of enteroviral hepatitis, especially HAV in pregnant women, is necessary, and therefore, proactive measures, such as promoting education, improving people awareness, and vaccination, are recommended.